The year of the Yao - Stern, James D.; Del Deo, Adam.; Venable, James L.; Werner, Jeff.; Tolajian, Michael; Fine Line Features; Endgame Entertainment (Firm); NBA Entertainment, Inc. ([Burbank, CA] New Line Home Entertainment, 2006)
"This documentary tells a unique story of eastern and western culture merging within the word of professional basketball. Yao Ming, the seven-feet-six-inches-tall athlete who is a star in his native China, was the first of the Houston Rockets for the 2002-2003 NBA draft. Feeling pressure from his chinese audience to succeed in the US, while simultaneously facing the scrutiny of the American basketball establishment, Yao meets significant challenges during his first year in the NBA. Narrated by Yao's 28-year-old interpreter, Colin Pine, the film shows how Yao and Colin navigate the turbulent ups and downs of American-style celebrity. Meanwhile, Colin also struggles with the complexity of translating NBA terminology into Mandarin Chinese. Despite frustrating setbacks and missteps, both Yao and Colin handle their new environments with aplomb and humor. Learning as they go, both become highly competent at what they do, finding ways to help each other. As a result, THE YEAR OF THE YAO is not only about basketball, it is also about the strong friendship that develops between these two strangers from totally different corners of the world."--Cover.
Originally released in 2005.
Music by, James L. Venable ; edited by, Jeff Werner and Michael Tolajian.
Yao Ming.
English dialogue with optional English or Spanish subtitles; closed-captioned.
Keywords: Yao, Ming -- 1980-.; Basketball players -- United States -- Biography; Basketball players -- China -- Biography